IMPLEMENTASI VIDEO FEEDBACK DALAM MENINGKATKAN KETERAMPILAN TEKNIK FOREHAND TENIS MEJA PADA SISWA KELAS V SD NEGERI 01 PONDOK PUCUNG - Acep Rohmat Nurhidayat; Veni Elisyah; Wendri Maryadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This classroom action research aimed to improve students’ forehand technique skills in table tennis through the implementation of video feedback among fifth-grade students of SDN 01 Pondok Pucung. The problem identified was the low mastery of forehand technique, as only 35.7% of students achieved the minimum mastery criterion. The study was conducted in two cycles consisting of planning, action, observation, and reflection stages, involving 28 students. Data were collected through performance assessment, observation, documentation, and teacher reflection notes. The results indicated an improvement in learning outcomes, shown by the increase in the mean score from 72 in Cycle I to 81 in Cycle II. Mastery learning improved from 57% in Cycle I to 82% in Cycle II, exceeding the classical mastery criterion of 75%. In addition to academic improvement, students demonstrated higher engagement and motivation during the learning process. Therefore, the implementation of video feedback is considered an effective instructional strategy to enhance motor skill acquisition in elementary physical education.